Gulayan Sa Paaralan (School Garden) Program Coordinators Production Practices: Basis for Capacity-Building Program - Ibañez, Jr. , Roger Y.; Velza, Jacob Frederick; Bartolay, Riza A. (Future Science / FSH-PH Publications, 2023)
Malnutrition is a pressing concern in the Philippines, and the Gulayan sa Paaralan Program (GPP) was initiated to combat this issue. This study aimed to investigate the production techniques employed by GPP coordinators in their various school gardens in connection with the school-based feeding program. The study employed a descriptive survey research design and collected data through a survey questionnaire administered to 49 GPP coordinators in the Municipality of Cawayan. Descriptive statistics such as frequency, percentage, mean, and standard deviation were used to analyze the collected data. The findings showed that the majority of GPP coordinators utilized organic fertilizers in their school gardens, and the most commonly grown vegetables were pechay, tomatoes, and eggplants. Nevertheless, the coordinators faced several challenges, including managing pests and diseases, and procuring sufficient resources such as water, labor, and tools. The study recommends training GPP coordinators on good agricultural practices, establishing a community-managed school garden system, and allocating adequate resources for the program's sustainability to address these challenges. The study's results demonstrate that the successful implementation of GPP in schools can lead to increased vegetable output and the eradication of malnourished children in schools. As a result, supporting and strengthening the GPP program is critical to combating malnutrition in the Philippines. The study's findings provide valuable insights for policymakers and stakeholders interested in developing and improving the GPP program. Overall, this study serves as a foundation for future research and interventions aimed at reducing malnutrition and improving food security in the Philippines.